2016
DOI: 10.15537/smj.2016.4.15018
|View full text |Cite
|
Sign up to set email alerts
|

The association between body mass index and duration spent on electronic devices in children and adolescents in Western Saudi Arabia

Abstract: Objectives:To evaluate the relationship between body mass index (BMI) and the duration spent on electronic devices, and to assess the factors that can cause obesity among children.Methods:A cross-sectional study including 541 participants. Data was collected from March to June 2015 via ambulatory pediatric clinics in Jeddah, Kingdom of Saudi Arabia. The BMI standard deviation was calculated based on Center of Disease Control and Prevention (CDC) standards.Results:The mean age of the participants was 10.1 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 14 publications
3
30
4
2
Order By: Relevance
“…For example, girls were more likely to own a smartphone but were less likely to own a computer and laptop, in addition to boys spending less time daily on electronic devices. A recent study from the Western region of Saudi Arabia showed a positive relationship between the time spent using electronic devices and BMI [28]. Furthermore, our study girls were less likely to eat fruits and vegetables but were more likely to eat potato chips and fast food frequently compared to boys.…”
Section: Discussionsupporting
confidence: 55%
“…For example, girls were more likely to own a smartphone but were less likely to own a computer and laptop, in addition to boys spending less time daily on electronic devices. A recent study from the Western region of Saudi Arabia showed a positive relationship between the time spent using electronic devices and BMI [28]. Furthermore, our study girls were less likely to eat fruits and vegetables but were more likely to eat potato chips and fast food frequently compared to boys.…”
Section: Discussionsupporting
confidence: 55%
“…AlGhamdi reported significant findings association of TV watching and obesity in children of Saudi Arabia [50]. Al-Agha et al concluded that children spending more than 2 hours of watching TV are associated with increased BMI [51]. A recent study done by Alghadir et al reported that children with moderate and active physical scores demonstrated less sedentary behavior (TV viewing and computer usage), lower body composition values, and higher total energy expenditure than sedentary or mild activity level participants [24].…”
Section: Sedentary Behavior Characteristicsmentioning
confidence: 99%
“…Childhood obesity is one of the most serious health conditions affecting many countries in the World [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%